Льохи стародавнього Києва кінця Х — першої половини ХІІІ ст. - Ієвлев, М.М.; Козловський, А.О. (Археологія, 2011)
Публікуються матеріали трьох льохів (порубів), виявлених на території Верхнього Києва. Рассмотрен один из малоизученных типов хозяйственных построек для хранения пищевых припасов. Различные типы таких хозяйственных построек на территории Киевской Руси в настоящее время достаточно хорошо известны. Однако такие хозяйственные постройки как погреб на территории Киева древнерусского времени практически не сохранились. В древнерусских письменных источниках встречаются упоминания про погреба и порубы на территории больших усадеб (княжеских, боярских, монастырских или купеческих). Судя по летописным и археологическим данным, над погребом возводили помещение. В нем складировали различные припасы, хранение которых не требовало низких температур. Вместе они образовывали хозяйственную постройку, которая в летописях получила название поруб. Сравнивая описания этих хозяйственных построек в летописях, необходимо отметить, что до ХІ в. в них встречались названия как погреб, так и поруб, а с ХІІ в. — только поруб. Несколько построек такого типа за последние годы открыто на территории Верхнего города Киева. Главной их особенностью было то, что они вырыты в материке и практически без крепления. В одном случае погреб был перекрыт деревом, засыпанным сверху грунтом. В настоящее время на территории Верхнего Киева открыто четыре таких погреба: один по ул. Большая Житомирская, 2а, два по ул. Артема, 12 и один по Десятинному переулку, 3. Наилучше сохранился погреб по ул. Большая Житомирская, 2а. Три погреба имели достаточно большие размеры: 15—20 м2 . Они находились на территориях усадеб: два на боярских и один, вероятно, на монастырской. Эти постройки подтверждают летописные и былинные сведения относительно конструкций и размеров погребов. Над двумя из них, вероятно, были наземные постройки (порубы). One of the little studied types of husbandry buildings for provisions storage is discussed. Various types of such husbandry buildings made on the territory of Kyiv Rus are well known by this time. However, it should be noted that such husbandry structures as cellars almost have not preserved on the territory of Kyiv. There are records in Ancient Rus written sources of cellars and frames on the territory of large estates (princes’, boyars’, merchants’ and in monasteries). Judging from chronicles and archaeological data, the surface part of cellar was erected over the underground one. Various provisions which did not require low temperatures were stored in the overland part. These parts together formed a separate husbandry structure which in chronicles bore the name «a frame». Comparing descriptions of these husbandry structures in the chronicles, it should be noted that before the 11th c. both names, «cellar» and «frame», were used, while since the 12th c. only «frame» was used. Several structures of such type were discovered on the territory of Upper Kyiv city in recent years. Their main feature is the fact that they are holed in subsoil and almost did not have bonding. In one case a cellar was overlapped with wood, which was covered with soil. Four such cellars are discovered on the territory of Upper Kyiv by this time: one at 2a Velyka Zhytomyrska Street, two at 12 Artema Street, and one at 3 Desyatynnyi Lane. A cellar at 2a Velyka Zhytomyrska Street is the best preserved. Three cellars were quite large: 15—20 m². They situated on the territories of estates: two were boyars’ and one was apparently at the monastery. These buildings confirm evidence from the chronicles and bylynas concerning cellars’ structure and size. Overland structures (frames) apparently existed over the two of them.